Expanding Indications of TIPS in the Management of Portal Hypertension Complications - Vulasala, Sai Swarupa Reddy; Onteddu, Nirmal Kumar Reddy; Kalva, Sanjeeva Prasad; Smolinski-Zhao, Sara (Journal of Clinical Interventional Radiology ISVIR, 2022)
Transjugular intrahepatic portosystemic shunt (TIPS) is a nonsurgical intervention to reduce portal pressure by creating a low-resistance channel between the portal and systemic circulations. It is a well-accepted treatment for gastroesophageal varices and refractory ascites. This review aims to discuss the evidence-based applications of TIPS in other complications of portal hypertension beyond gastroesophageal varices and refractory ascites.
Keywords: portal hypertension; TIPS; expanding indications of TIPS